PENGARUH KEPEMIMPINAN, DUKUNGAN ORGANISASI DAN KEADILAN TERHADAP KINERJA PEGAWAI BPJS KESEHATAN KANTOR CABANG LHOKSEUMAWAE - Zulikhwan . (Universitas Islam Islam Sumatera Utara, 2020)
An employee who feels that his work and work has the support of an organization that is and in accordance with what he hopes will definitely feel dissatisfied with the support carried out by the organization or agency where it works. The problems faced by employees in the Social Security Assurance Agency (BPJS) of the Lhokseumawe Branch Office where leadership has still not been able to implement optimizing all working human resources due to the kinship between workers and local officials so that organizational support is not based on work results and this relates to giving value to the work done by employees so as to cause a sense of injustice among employees. The sample in this study amounted to 58 people. Y = 5.271 + 0.083X1 + 0.833X2 + 0.331X3. The multiple linear regression equation can be interpreted as follows: If the variable workload, Justice, and work environment 5,271 is equal to zero, then the performance will be worth as much as a unit with a tendency to decrease. If the workload variable is increased by 1 unit, the teacher's performance will increase by 0.083 units. If Justice is increased by 1 unit, it will be followed by an increase in teacher performance by 0.833 units.If the work environment is improved by one unit, it will be followed by an increase in performance by 0.331 units